Exploring the α-Amylase Inhibitory Potential of Peronema canescens Jack: An In Vitro and In Silico Study - Rahardhian, Muhammad Ryan Radix; Aryanti, Ninda; Susilawati, Yasmiwar; Sumiwi, Sri Adi; Putri, Chintiana Nindya; Ramonah, Dewi; Suharsanti, Ririn (HAYATI Journal of Biosciences, 2025)
Hyperglycemia in individuals with type 2 diabetes mellitus is primarily driven by the rapid hydrolysis of starch by the enzyme α-amylase in the pancreas and the breakdown of oligosaccharides by α-glucosidase in the intestine. Peronema canescens Jack. (PC) has shown promise as a potential antidiabetic agent. This study aimed to evaluate the total flavonoid, phenolic, and α-amylase inhibitory activity of extracts and fractions derived from PC leaves using both in vitro and in silico approaches. The ethanol extract of PC leaves was fractionated through liquid-liquid extraction using n-hexane, ethyl acetate, and water as solvents. Preliminary phytochemical screening of the extracts and fractions identified the presence of alkaloids, flavonoids, saponins, tannins, and steroids/triterpenoids. The n-hexane fraction exhibited the highest total flavonoid content, averaging 203.37±4.38 mg QE/gram, while the ethyl acetate fraction demonstrated the highest total phenolic content, averaging 147.04±0.79 mg GAE/gram. Furthermore, the ethyl acetate fraction showed the strongest α-amylase inhibitory activity, with an average inhibition rate of 70.38±1.26%. In silico analysis, combined with GC-MS identification, suggested that three compounds, bis(2-ethylhexyl) phthalate, myristyl oleate, and 14 beta H-pregna may contribute to the observed α-amylase inhibitory activity. These findings highlight the potential of PC as a source of natural antidiabetic agents.